Density‐driven water circulation in a typical tributary of the Three Gorges Reservoir, China. (7th June 2019) - Long, Lianghong; Ji, Daobin; Yang, Zhengjian; Ma, Jun; Wells, Scott A.; Liu, Defu; Lorke, Andreas
Abstract: A 2‐D hydrodynamic model was developed for modelling water circulation from 2008 to 2011 in a typical tributary of the Three Gorges Reservoir. The model is capable of describing flow behaviour and mixing mechanisms for different density current patterns and performs well in computing the velocity, the intrusion layer at the plunge point, and the travel distance of the density current. The effects of 10 flow patterns on thermal stratification, hydrodynamics, and algal bloom risk are discussed and classified in terms of algal growth. Patterns (6) and (10) can effectively prevent algal blooms; Patterns (7) and (8) are good for algal blooms. More frequent transformations of flow‐driven patterns, as observed in 2010–2011, could create more eddies and mixing and thus reduce bloom risk. Further studies are necessary and recommended for more accurate predictions, assessing the impact of water level fluctuations on transform flow patterns and water quality.